Faktor-Faktor yang Berhubungan dengan Kualitas Hidup Penderita Rheumatoid Arthitis: Sebuah Tinjauan Sistematis - Yofa Anggriani Utama (Universitas Batanghari Jambi, 2022)
Rheumatoid Arthritis is an autoimmune disease in which the joints of the hands and feet become inflamed, causing swelling, pain and evetually causing damage to the inside of the joints. The purpose of this study was to determine the factor associated with the Quality of Life Rheumatoid Arthritis patients. The research design included in this systematic review uses a research design, namely quantitative methods. Bades on the results of systematic review, it was found that the factor related to the Quality of Life Rheumatoid are health identity, disease activity and education, role limitations, due to physical, emotional problems, blood pressure, age group, marital identity, place of residence, monthly income, length of stay, illnes and type of treatment. Psychological factors andpain, social support, receiving treatment, restriction of movement and joint deformity, daily activities, pain, stiffnes, fatique and sleep disturbances, managing pain well, bein able to control stress well and having family support and availability informasi, loneliness factor. It is haoped that it can provide support in the form of health care facilities, maintain a healthy lifestyle, and provide information about Rheumatoid Arthritis